Histórias de homoparentalidade adotiva : contribuições do modelo bioecológico - Tsuchiya, Daniela Yumi (2019)
The senses and meanings around sexuality, parenting and family were built and reconstructed throughout history of humanity. Dimensions such as being linked to the attainment of pleasure are largely recorded, however over the centuries, with religious, economic and political interference in almost all Western civilization, sexuality has become prominent for the reproduction of the human species, and consequently has brought new meanings which pass through and affect society until the present day.This research presents the historical contextualization of sexuality in the West, the current legislation and psychological aspects involved in adoptive homoparentality, seeking to reposition the view on adoption to the importance of affective bonding and family cohesion. The study aimed to investigate two adoptive homosexual couples (one with adopted children and the other adopting) as they experience this whole process, from the family construction, through educational practices of their parents and also through educational practices that play and / or intend to play. The analysis presented is based on the Bioecological Model of Human Development, which analyzes the multidirectional, interrelated dimensions present in the life of each individual, represented by the PPCT - Person, Process, Context and Time. The research brings information by the following instruments: script of semi-structured interview, Scripts with daily situations of the socialization of children based on instruments such as the Test of Incomplete Stories (MONDELL & TYLER, 1981; adapted by CECCONELLO, 2003) and a Descriptor of emotions and feelings in educational practices. The results show the pairs surveyed bringing reports in which it was possible to identify normative positions regarding what is thought and done for the children and much of their subjectivation and imaginary processes linked to the family constitution still seem to be coordinated by heteronormativity. Regarding the practices they carry out and intend to play, they emphasized the importance of education and concern / care / respect with each other. They elucidated what each one had as teaching at home, pointing out what they have learned and intend to repeat or not, what they consider to be healthy for the family, each completing and seeking the best for the balance of the home, being programmed and organize themselves for it. We discuss the need to reflect the contents that are interrelated throughout the development and subjectivation of each in fluent disalienation and empowerment, and as regards parenthood.